Longitudinal variance of Donor‐Derived Cell‐Free DNA (dd‐cfDNA) in Stable Kidney Transplant (KTx) patients are influenced by donor/recipient variables. Issue 9 (4th July 2021) - Anand, Sanjiv; Lopez‐Verdugo, Fidel; Sanchez‐Garcia, Jorge; Dong, Li; Fife, Megan; Krong, Jake; Morris, Donald; Srinivas, Titte R.
Abstract: Background: The longitudinal time‐course of dd‐cfDNA after kidney transplant (KTx) is not well‐described. The cut off values of dd‐cfDNA in KTx derive from biopsy‐coupled single measurements. Meaningful interpretation necessitates understanding of: (1) time variance of dd‐cfDNA levels post‐KTx, (2) factors determining biologic variability, and (3) relationship to donor and recipient characteristics. We hypothesized that an understanding of the aforementioned factors would better inform clinical decision‐making using dd‐cfDNA. Methods: One hundred and twenty five KTx patients with dd‐cfDNA obtained longitudinally were included. Univariate analyses were directed at inter‐patient variability and intra‐patient inter‐occasion variability of dd‐cfDNA. Multivariate linear regression was used in analyses accounting for repeat measures. Results: At 1‐month post KTx median dd‐cfDNA: (1) were higher in repeat KTx (.57%, P < .001), and dual KTx (1.10%, P = ns) versus a first KTx (.31%); (2) showed a significant difference in donor after cardiac death (DCD [.45%]) versus living related (LRD [.27%]) donors ( P = .036). Longitudinal (1–3 months) dd‐cfDNA measurements showed a significant downtrend for all donor types. Panel‐reactive antibodies (PRA) were positively correlated with dd‐cfDNA. Conclusions: Repeat Tx, dual Tx, DCD, and PRA are associated with a higher dd‐cfDNA. Incorporation of donor/recipient variables and time down post transplant is material for rational interpretation of dd‐cfDNA.